2018
DOI: 10.1021/acs.jnatprod.8b00519
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of β-Mangostin by an Endophytic Fungus of Garcinia mangostana to Furnish Xanthenes with an Unprecedented Heterocyclic Skeleton

Abstract: Biotransformation of β-mangostin (1) by the endophytic fungus Xylaria feejeensis GM06 afforded hexacyclic ring-fused xanthenes with an unprecedented hexacyclic heterocylic skeleton. β-Mangostin (1) was transformed to two diastereomeric pairs of enantiomers, mangostafeejin A [(−)-2a/(+)-2b)] and mangostafeejin B [(−)-3a/(+)-3b)]. The chemical structures of the transformation products were elucidated by analysis of NMR and MS data, and the structure of mangostafeejin A [(−)-2a/(+)-2b)] was confirmed by single-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Xylaria feejeensis is biologically associated with the mangosteen fruit and was thus examined for its capability to biotransform plant metabolites to novel derivatives [58]. One of the secondary metabolites produced by said plant is the xanthone β-mangostin, which is associated with anti-inflammatory, antibacterial, antimalarial, and antimycobacterial activities.…”
Section: Benzenoids and Lactones From Xylariaceae (Fig 7)mentioning
confidence: 99%
“…Xylaria feejeensis is biologically associated with the mangosteen fruit and was thus examined for its capability to biotransform plant metabolites to novel derivatives [58]. One of the secondary metabolites produced by said plant is the xanthone β-mangostin, which is associated with anti-inflammatory, antibacterial, antimalarial, and antimycobacterial activities.…”
Section: Benzenoids and Lactones From Xylariaceae (Fig 7)mentioning
confidence: 99%
“…The relative stereochemistry of 2 was established by comparing the observed coupling constants and NOE data with those of harzialactone A isolated from Trichoderma harzianum OUPS-N115. 17 Namely, its coupling constant magnitude of H-3 with H-2 and H-4 (J 2,3α = J 2,3β = J 3β,4 = 8.2 Hz and J 3β,4 = 3.3 Hz; Table 2) was closely similar to that of harzialactone A (J 2,3α = J 2,3β = J 3β , 4 = 8.3 Hz and J 3β,4 = 3.5 Hz). 18 Furthermore, NOEs of H-4 with H-3β and of H-2 with H-3α and H-5 in the NOESY spectrum of 2 (Figure 2) agreed with those of harzialactone A.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Biotransformation has advantages over conventional chemical synthesis due to its selective nature, environmental acceptability, mild conditions, and high reaction rates. 16,17 Biological assay revealed that compounds 1, 3, 5, and 6 inhibit the growth of the crop pathogenic microbes Xanthomonas oryzae pv. oryzae (Xoo) and X. oryzae pv.…”
mentioning
confidence: 99%
“…being determined by using the helicity rule for α,β-unsaturated ketone. Compounds 493a/493b and 494a/494b, as xanthene enantiomers with an unprecedented hexacyclic heterocylic backbone, were isolated from Xylaria feejeensis GM06 in 2018 [236]. The abs.…”
Section: Nonalkaloidsmentioning
confidence: 99%